Inactivation of Escherichia coli, F′ Episomes at Transfer, and Bacteriophage Lambda by Psoralen Plus 360-nm Light: Significance of Deoxyribonucleic Acid Cross-Links - Cole, Ronald S. (1971)
We have investigated some biological consequences of light-induced psoralen-deoxyribonucleic acid (DNA) adducts and find that for several Escherichia coli functions (killing of strain AB2480 recA13 uvrA6, inactivation of phage lambda plaque-forming ability in wild type and uvrA6 hosts, loss of ability to transmit intact Flac(+) episomes), a light exposure sufficient for production of a single cross-link per DNA molecule correlates well with the biological consequence. Although one cross-link per genome is apparently lethal to recA13 uvr(−) strains, mutants carrying the recA13 or uvrA6 markers survive light exposures producing 6.7 and 16 cross-links per genome, respectively, and wild-type cells recover from 65 psoralen cross-links. Evidently, the excision and recombinational repair systems complement one another in reconstructing an intact genome from cellular DNA containing psoralen photoproducts. The above bacterial and phage strains, in which DNA repair processes are minimized, are also extremely sensitive to pyrimidine dimer-forming 254-nm UV light (without psoralen), and were expected to respond similarly to formation of psoralen-pyrimidine base monoadducts in their DNA. Since the biological inactivation by psoralen correlates well with cross-link formation, we suggest that the sensitizing action of this drug primarily derives from its ability to form DNA cross-links.